2009
DOI: 10.1097/nen.0b013e3181996d8f
|View full text |Cite
|
Sign up to set email alerts
|

TAR DNA-Binding Protein 43 Accumulation in Protein Aggregate Myopathies

Abstract: Protein aggregate myopathies, including myofibrillar myopathies and sporadic inclusion body myositis (sIBM), are characterized by abnormal protein aggregates composed of various muscular and ectopic proteins. Previous studies have shown the crucial role ofdysregulated transcription factors such as neuron-restrictive silencerfactor in the expression of aberrant proteins in myotilinopathies. Here, we assessed possible aberrant expression of TAR DNA-bindingprotein 43 (TDP-43), another factor involved in transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 66 publications
7
77
1
Order By: Relevance
“…Similar discrepancies were reported in myopathies, 18 that is, not all TDP-43-positive deposits were stained with anti-pTDP-43 antibodies, and not all pTDP-43-positive inclusions were recognized by anti-TDP-43 antibodies in protein-aggregate myopathies.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Similar discrepancies were reported in myopathies, 18 that is, not all TDP-43-positive deposits were stained with anti-pTDP-43 antibodies, and not all pTDP-43-positive inclusions were recognized by anti-TDP-43 antibodies in protein-aggregate myopathies.…”
Section: Discussionsupporting
confidence: 70%
“…However, general organs outside the CNS have rarely been studied regarding the accumulation of TDP-43. In general human organs, TDP-43 accumulates frequently in the cytoplasm of the muscles of patients with sporadic inclusion body myositis and oculopharyngeal muscular dystrophy, and in other protein-aggregate myopathies; 18 however, TDP-43 accumulation has not been reported in other general human organs. Recently, the TDP-43 profile was investigated using Western blot analysis in lysates of circulating lymphocytes, which showed that TDP-43 was expressed at approximately the same levels in whole lymphocyte lysates of ALS patients, their relatives, and controls.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1H), synemin, Xin, TAR DNA-binding protein 43 (TDP-43), and co-chaperones including αB-crystallin (Fig. 1E), heat shock protein (Hsp) 27 ( Fig.1I) and DNAJB2 [8][9][10][11][12][13][14][15][16]. Additional abnormal accumulation of several other proteins was documented in myotilinopathy and desminopathy.…”
Section: Pathologic and Clinical Features 21 Morphologymentioning
confidence: 99%